Gender Discrimination in Competitive Markets - Sugata Marjit; Reza Oladi (Center for Economic Studies and ifo Institute (CESifo), 2022)
We propose a competitive general equilibrium theory of gender discrimination in labor market where male and female workers are equally productive, but the female workers are deliberately paid less than the male due to subjective discrimination. Pioneering works of Becker (1957) and Arrow (1973), in terms of partial equilibrium models, have argued that the forces of competition would restrict subjective discrimination which leads to increasing cost for a firm and reduce the return to capital. In contrast, using a general equilibrium framework as in Jones (1965), we show that discrimination can perpetuate even in perfectly competitive markets. We also show that the return to capital can increase with discrimination if the capital intensive sector is also female worker dominated. If international trade policy, or any competitive price shock, reduces return to capital, increasing discrimination may be attempted to compensate the capital. Thus, policy intervention may be essential to contain discrimination in competitive markets.
Keywords: J16; J70; 330; gender discrimination